Confusion in a patient with premature ventricular complexes originating in the left ventricular summit. Issue 4 (28th March 2023) - Luani, Blerim; Schmeisser, Alexander; Wiemer, Marcus; Braun-Dullaeus, Rüdiger C
Abstract: Background: Premature ventricular complexes (PVCs) originating in the ventricular outflow tracts are mostly of benign character. Case Summary: We describe a rare case of pulmonary hypertension with severe hypoxaemia and confusion caused by a significant mitral regurgitation (MR) during PVC originating in the left ventricle summit. After successful PVC ablation, all above-mentioned clinical parameters had normalized. Discussion: Premature ventricular complexes originating in the outflow tracts should be considered as a potential though rare cause of severe MR and pulmonary hypertension.